Multimodality Imaging in a Patient with Erdheim Chester Disease with Cardiovascular Involvement - Jagia, Priya; Ojha, Vineeta; Sharma, Gautam (Acta medica Lituanica, 2025)
We hereby report a 40-year-old woman presenting with chest pain and recurrent pericardial effusion. Cardiac MRI revealed diffuse sheath-like mass involving predominantly the right heart chambers. She also had bony and perirenal involvement. Additionally, she had a pineal gland tumor, a biopsy from which revealed xanthogranulomatous infiltration with foamy histiocytes which were CD 68 positive and CD1a negative, diagnostic of Erdheim Chester disease. Erdheim Chester disease is a rare form of non-Langerhans cell histiocytosis. We highlight the importance of multimodality imaging for comprehensive assessment of all the organ systems to enable prompt diagnosis of this rare condition.
Keywords: Erdheim Chester disease; multimodality imaging